2016
DOI: 10.1104/pp.15.01870
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Leaf Flecking in Maize and Its Relationship to Plant Defense and Disease Resistance

Abstract: Physiological leaf spotting, or flecking, is a mild-lesion phenotype observed on the leaves of several commonly used maize (Zea mays) inbred lines and has been anecdotally linked to enhanced broad-spectrum disease resistance. Flecking was assessed in the maize nested association mapping (NAM) population, comprising 4,998 recombinant inbred lines from 25 biparental families, and in an association population, comprising 279 diverse maize inbreds. Joint family linkage analysis was conducted with 7,386 markers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 109 publications
(148 reference statements)
0
20
0
Order By: Relevance
“…B), appearing in several widely used lines as well as in several other species such as barley (Makepeace et al , ), wheat (Nair and Tomar, ) and oats (Ferdinandsen and Winge, ). Recent work has indicated that in some cases flecking seems to be a mild form of misregulated HR (Olukolu et al , ; Vontimitta et al , ).…”
Section: Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…B), appearing in several widely used lines as well as in several other species such as barley (Makepeace et al , ), wheat (Nair and Tomar, ) and oats (Ferdinandsen and Winge, ). Recent work has indicated that in some cases flecking seems to be a mild form of misregulated HR (Olukolu et al , ; Vontimitta et al , ).…”
Section: Conceptsmentioning
confidence: 99%
“…These approaches generally failed since the disease resistance provided was insufficient or the yield penalties were too high (Hammond‐Kosack and Parker, ). Both mild and extreme leaf flecking (as described above) are associated with broad‐spectrum resistance (Olukolu et al , ). While more extreme flecking was also associated with a yield penalty, milder flecking was not.…”
Section: Consequencesmentioning
confidence: 99%
“…Association mapping studies have been widely reported for foliar diseases (Kump et al, 2011; Poland et al, 2011; Gowda et al, 2015; Olukolu et al, 2016), ear rot diseases (Zila et al, 2014; Warburton et al, 2015; Han et al, 2018), flowering time, and plant architecture (Wallace et al, 2016) in maize. In this study, we applied a comprehensive GWAS for popping expansion using 165,089 SNPs markers in 183 inbred lines with 2 yr of trial data.…”
mentioning
confidence: 99%
“…Olukolu et al 2013Olukolu et al , 2014Olukolu et al , 2016 and plant development(Buescher et al 2014), among…”
mentioning
confidence: 99%